2019
DOI: 10.18502/jovr.v14i3.4781
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Multidrug-resistant Pseudomonas Aeruginosa Endophthalmitis Due to Contaminated Trypan Blue Solution

Abstract: PurposeTo report the investigation of an outbreak of multidrug-resistant (MDR) Pseudomonas aeruginosa endophthalmitis in 13 patients after cataract surgery and to emphasize on the importance of clinical profile, risk factors, and treatment outcomesMethodsThis was a hospital-based, retrospective case study with 13 consecutive patients who had man- ual small-incision cataract surgery with intraocular lens (IOL) implantation and developed acute postoperative Pseudomonas aeruginosa endophthalmitis. The anterior ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This altercation might be due to the low human samples included in the study. Apart from the involvement of a broad range of cytokines, our transcriptomics data revealed the involvement of a large number of chemokines involved in causing a dysregulated immune response, which included CXCL ( 2 , 5 , 9 , 12 14 , 16 ), CCL ( 3 , 4 , 6 , 7 , 9 , 12 , 19 , 24 ), and CCR ( 2 , 5 ). While several studies have shown the affiliation of these chemokines with inflammation ( 28 ), not much has been described on its association with MDR P. aeruginosa infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This altercation might be due to the low human samples included in the study. Apart from the involvement of a broad range of cytokines, our transcriptomics data revealed the involvement of a large number of chemokines involved in causing a dysregulated immune response, which included CXCL ( 2 , 5 , 9 , 12 14 , 16 ), CCL ( 3 , 4 , 6 , 7 , 9 , 12 , 19 , 24 ), and CCR ( 2 , 5 ). While several studies have shown the affiliation of these chemokines with inflammation ( 28 ), not much has been described on its association with MDR P. aeruginosa infection.…”
Section: Discussionmentioning
confidence: 97%
“…This altercation might be due to the low human samples included in the study. Apart from the involvement of a broad range of cytokines, our transcriptomics data revealed the involvement of a large number of chemokines involved in causing a dysregulated immune response, which included CXCL (2,5,9,(12)(13)(14)16), CCL (3,4,6,7,9,12,19,24), and CCR (2,5). While several studies have MDR-PA triggers an initial response which leads to higher infiltration of leukocytes and macrophages in the vitreous cavity, followed by release of cytokines (IL-1b, IL-6, IL-1a, TNF-a, IL-18), chemokines (CXCL-5, CCL-6), MPO, granzyme, and MMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks of P. aeruginosa are mostly attributed to contaminated ophthalmic solutions and devices. 2 Because of the high virulence of this bacterium, the visual outcome is usually disappointingly poor despite prompt therapeutic interventions. A summary of recent relevant studies on post-cataract surgery endophthalmitis outbreaks caused by P. aeruginosa is provided in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 Although Gram-negative bacteria are found in only 6% to 29% of cases, major concerns include their more significant role in endophthalmitis outbreaks, high virulence, and undesirable visual outcomes despite immediate treatment. 2 An outbreak of this complication can be catastrophic for both patients and surgeons. Thus, recognition and correction of the cause are necessary in this situation.…”
Section: Introductionmentioning
confidence: 99%